2018
DOI: 10.1002/jgf2.230
|View full text |Cite
|
Sign up to set email alerts
|

Physical assessment by Japanese community hospital nurses compared to that performed overseas: A cross‐sectional study

Abstract: Background Japanese nurses may not be adequately trained to perform physical assessments compared to nurses overseas due to differences in accessibility to education; currently, research investigating this discrepancy is limited. This study investigated the current performance levels of Japanese community nurses in physical assessments and compared their performance to that of nurses overseas. Methods In this cross‐sectional study, we examined the practical application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
9
1
1
Order By: Relevance
“…The nurse-to-patient ratios were 1:10 for acute care, 1:13 for comprehensive care, 1:15 for rehabilitation, and 1:25 for chronic care. The hospital had 27 physicians, 197 nurses, 7 pharmacists, 15 clinical technicians, 37 therapists, 4 nutritionists, and 34 clerks [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The nurse-to-patient ratios were 1:10 for acute care, 1:13 for comprehensive care, 1:15 for rehabilitation, and 1:25 for chronic care. The hospital had 27 physicians, 197 nurses, 7 pharmacists, 15 clinical technicians, 37 therapists, 4 nutritionists, and 34 clerks [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Its total land area measures 553.1 km 2 , which accounts for 8.3% of Shimane Prefecture, most of which is covered by forest. A survey conducted in 2017 revealed that the total population of Unnan City was 38,882 (18,720 men and 20,162 women), with 37.82% being over 65 years of age [ 19 ]. Unnan City was the first city that applied LSG to communities in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…The city has 16 clinics, 12 homecare stations, three visiting nurse stations, and one public hospital [ 16 ]. When the study was conducted in 2018, Unnan City Hospital had 281 care beds, 27 physicians, 197 nurses, seven pharmacists, 15 clinical technicians, 37 therapists, four nutritionists, and 34 clerks [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the study ensured the reliability and validity of the UNNAN ladder, there was no correlation between years of experience and age in nursing practice ability, which suggested that independent self-improvement may not lead to an improvement in the nursing practice ability. In addition, in the research on the community hospital’s nurses’ physical skills assessment, clinical experience alone did not appear to improve their knowledge and skills [ 12 ].…”
Section: Introductionmentioning
confidence: 99%